SUPPLY CHAIN MANAGEMENT STRATEGY TO INCREASE AGRIBUSINESS EFFICIENCY - Tri Waluyo (Sean Institute, 2023)
The supply chain has a crucial role in supporting the smooth operation of agribusiness, which involves the production, distribution and marketing of agricultural products. Efficiency in the supply chain is the key to increasing the competitiveness of agribusiness in the global market. This research aims to analyze and evaluate supply chain management strategies in increasing agribusiness efficiency. This research uses a qualitative approach with descriptive methods. The research results show that implementing supply chain management strategies in agribusiness has a positive impact on operational efficiency and sustainability. The use of sensor technology, automation and data analysis helps increase agricultural productivity. Quality and sustainability certifications, as well as clear labeling, provide product transparency and increase consumer confidence. Strong partnerships with suppliers and distributors increase coordination and flexibility in dealing with market changes. Improved transportation management reduces costs and environmental impacts. Innovative marketing strategies, including online marketing and partnerships with retailers, succeeded in increasing product visibility and expanding market share. Thus, holistic implementation of these strategies can bring positive changes in improving the performance and sustainability of agribusiness supply chains.